Resolving salt-cocrystal conundrum in multicomponent crystals by using X-ray quantum crystallography - Sudheendranath, Athul; Tothadi, Srinu; Pradhan, Amit Kumar; Prajapati, Aditya Kumar; Nangia, Ashwini; Thomas, Sajesh P. (Journal of Physical Chemistry C, 2025)
The structural identity of multicomponent crystals as a salt or cocrystal is dictated by the proton transfer state between the molecular components. In pharmaceutical drugs, solid-state forms such as salts or cocrystals can have significantly distinct stability, dissolution, and solubility profiles. The accurate location of proton positions is a formidable task using conventional X-ray crystallography, as the atomic scattering factors are based on spherical electron density models. Herein, we demonstrate that the X-ray quantum crystallographic (QCr) technique of Hirshfeld Atom Refinement (HAR), based on aspherical atomic scattering factors, can be effectively employed to resolve this riddle. Our HAR models accurately located the proton positions, thus distinguishing salts, cocrystals, and continuum crystal structures, which are substantiated by the N 1s binding energies from X-ray photoelectron spectroscopy (XPS) corresponding to the base components in a series of crystals. The QCr models reveal the subtle features of electron localization and bonding around the double-well potential in the intermolecular proton-transfer regions in these crystals.